Estimativa das emissões de gases de efeito estufa em uma propriedade leiteira da região centro-oriental do estado do Paraná: estudo de caso - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
Brazil stands out in the global agricultural sector, which significantly contributes to greenhouse gas (GHG) emissions, particularly carbon dioxide (CO2), nitrous oxide (N2O), and methane (CH4). Given growing concerns about global warming, there is an increasing need to develop tools and strategies to reduce these emissions. This study analyzed GHG emissions in dairy farming on a property in Paraná, applying the GHG Protocol to quantify and manage these emissions. The annual inventory revealed total emissions of 935.8 tons of CO2-eq, with removals of 611.91 tons, resulting in a net balance of 322.19 tons of CO2-eq. The primary emission source was enteric fermentation (90.7%), followed by manure management (5%), organic fertilization (1.7%), and mechanized operations (1.3%). The research identified mitigation strategies such as using biodigesters for manure management, which could reduce emissions by up to 0.73%, while also generating biogas and biofertilizers. Dietary adjustments and feed additives were also suggested to reduce methane emissions. In corn production, the farm’s main agricultural activity, residues and fertilization accounted for 103.11 tons of CO2- eq over 42 hectares, below the national average. Indirect emissions from transportation totaled 3.21 tons of CO2-eq per year. With eucalyptus planting and preservation areas, the farm sequestered 611.91 tons of CO2-eq annually, contributing to a negative carbon balance. Simulations indicated that the combined adoption of a biodigester, electric tractors, and a silvopastoral system would reduce the farm’s emissions by 83.28%, totaling 54.13 tons of CO2- eq per year. The study concluded that promoting family farming and low-impact practices is essential for the sustainability of dairy production in Brazil.
Keywords: Agronegócio; Inventário de Emissões e Sustentabilidade; Engenharia Sanitária e Ambiental